Design process innovation on brock commons tallwood house. Issue 1 (3rd August 2021) - Poirier, Erik; Staub-French, Sheryl; Pilon, Angelique; Fallahi, Azadeh; Teshnizi, Zahra; Tannert, Thomas; Froese, Thomas
Abstract : Purpose: The purpose of this paper is to study the design process innovations that enabled the successful delivery of a hybrid, mass-timber high-rise building in Canada, the Brock Commons Tallwood House at the University of British Columbia. It is one of a set of papers examining the project, including companion papers that describe innovations used during the mass timber construction process and the impact of these innovations on construction performance. Design/methodology/approach: A mixed-method, longitudinal case study approach was used in this research project to investigate and document the Tallwood House project over a three-year period. Both quantitative and qualitative data collection and analysis techniques were used. Graduate student researchers were embedded within the project team to observe meetings and decision-making and to conduct periodic interviews. Findings: The research highlights a case of a balanced triple-helix system that provided a context for the successful "clustering" of product and process innovation, which were developed and implemented to flow throughout the project's lifecycle and across its supply chain to provide benefits at each stage. Four significant process-based innovations were implemented at the design phase of the building project to support radical product innovation: an integrated design process, virtual design and construction, designing for manufacturing and assembling and a rigorous quality control and quality assurance process. The product innovations developed through these process innovations were the structural system and the prefabricated envelope system. The context of innovation was seen to allow this "clustering, " which is believed to be a key condition of success and enabled the efficient and successful delivery of the project. Generally, the approach was successful; however, some factors including the number of stakeholders and good-faith collaboration may limit the replicability of these strategies. Originality/value: This paper presents an in-depth investigation into the instantiation of an innovation system, identified as a balanced triple-helix system, which enabled and facilitated the design and decision-making process for a radical product innovation. Moreover, this paper describes the deployment of a "cluster" of process innovations that flowed throughout the project's lifecycle and across the project supply chain. This was seen as a key factor in ensuring the successful delivery of the project.